2013
DOI: 10.1371/journal.pone.0083502
|View full text |Cite
|
Sign up to set email alerts
|

Rheostats and Toggle Switches for Modulating Protein Function

Abstract: The millions of protein sequences generated by genomics are expected to transform protein engineering and personalized medicine. To achieve these goals, tools for predicting outcomes of amino acid changes must be improved. Currently, advances are hampered by insufficient experimental data about nonconserved amino acid positions. Since the property “nonconserved” is identified using a sequence alignment, we designed experiments to recapitulate that context: Mutagenesis and functional characterization was carrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
229
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 67 publications
(242 citation statements)
references
References 51 publications
(89 reference statements)
13
229
0
Order By: Relevance
“…To develop the RheoScale calculator, we used both simulated data (Figure and ) and experimental data previously published for the LacI/GalR paralogs (Meinhardt et al., ). We further tested the calculator on published data for pyruvate kinase, an enzyme for which multiple experimental functional parameters are available (Ishwar et al., ; Tang et al., ), and three TIM barrel orthologs that were characterized using deep mutational scanning (Chan et al., ).…”
Section: Example Applicationsmentioning
confidence: 99%
See 3 more Smart Citations
“…To develop the RheoScale calculator, we used both simulated data (Figure and ) and experimental data previously published for the LacI/GalR paralogs (Meinhardt et al., ). We further tested the calculator on published data for pyruvate kinase, an enzyme for which multiple experimental functional parameters are available (Ishwar et al., ; Tang et al., ), and three TIM barrel orthologs that were characterized using deep mutational scanning (Chan et al., ).…”
Section: Example Applicationsmentioning
confidence: 99%
“…Both of these expected scenarios tempt investigators to extrapolate the outcome from one variant (or a few) to the overall role of the position being substituted (neutral or toggle). However, this inference is not appropriate for a third class of protein positions: We observed this class in an experimental study of select nonconserved positions in LacI/GalR homologs (Meinhardt & Swint‐Kruse, ; Meinhardt et al., ; Tungtur, Egan, & Swint‐Kruse, ; Tungtur, Meinhardt, & Swint‐Kruse, ; Tungtur, Parente, & Swint‐Kruse, ). Many substitutions did alter protein function which indicated that, despite their nonconservation, these positions were important (and thus, not neutral).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another ~1100 variants are from in vivo and biochemical studies of LacI/GalR chimeras [21,2629]. The remaining variants are from biochemical studies of LacI, PurR, GalR, CytR, FruR and CcpA.…”
Section: Resultsmentioning
confidence: 99%